Analysis and Design of Machine Elements - Jiang, Wei (Wiley, 2019)
Incorporating Chinese, European, and International standards and units of measurement, this book presents a classic subject in an up-to-date manner with a strong emphasis on failure analysis and prevention-based machine element design. It presents concepts, principles, data, analyses, procedures, and decision-making techniques necessary to design safe, efficient, and workable machine elements. Design-centric and focused, the book will help students develop the ability to conceptualize designs from written requirements and to translate these design concepts into models and detailed manufacturing drawings.